Novel in vitro methodology for induction of Enterococcus faecalis biofilm on apical resorption areas - Albuquerque, Maria Tereza Pedrosa [UNESP]; Junqueira, Juliana Campos [UNESP]; Coelho, Marcella Batista Pavanello [UNESP]; De Carvalho, Claudio Antonio Tauge [UNESP]; Valera, Marcia Carneiro [UNESP] (Wolters Kluwer, 2014)
Context: Teeth with periapical lesion usually present external root resorption around the apical foramen. These areas facilitate adhesion and co-aggregation of microorganisms developing biofilms. Up to the present moment, there is no methodology in the literature that enables the in vitro evaluation of endodontic irrigants and intracanal dressings on biofilms located in apical external root resorptions of human teeth. Aims: This study aimed to describe a new in vitro methodology for Enterococcus faecalis biofilm development in external apical reportion areas of human extracted teeth in different periods of time. Settings and Design: In vitro qualitative laboratory study. Subjects and Methods: Thirty roots from human extracted teeth presenting external apical resorption had their root canal diameters standardized by means of instrumentation. Next, the roots were randomly divided into three groups (n = 30) according to E. faecalis strains (ATCC 29212) exposure time as follows: Group T5, with 5-day exposure; Group T10, with 10-day exposure, and Group T15, with 15-day exposure. The roots were attached to 24-well culture plates so that only their apices could be in contact with bacteria for induction of biofilm formation. At the end of these exposure times, the roots were qualitatively evaluated with scanning electron microscope to observe the presence of biofilm in external resorptions around the apical foramen. Results: It was found that microorganisms were present in all exposure times, although structures suggesting the presence of biofilm with great conglomerate of bacteria showing structures similar to polysaccharide extensions were observed at the 10 th day of exposure. Conclusions: By means of this new methodology, it was possible to observe biofilm formation in the areas of external apical resorption after 10 days of exposure.
Keywords: Biofilm; Enterococcus faecalis; external resorption